Promoting the practice of exclusive breastfeeding: a philosophic scoping review - Tumilara Busayo Amoo; Tosin Popoola; Ruth Lucas (BMC, 2022)
Abstract Background The World Health Organization recommends exclusive breastfeeding for the first 6 months of an infant's life and continued breastfeeding for 2 years. The global rate of exclusive breastfeeding is low at 33%. Thus, it is important to identify philosophical and theory-based strategies that can promote exclusive breastfeeding. The aim of the study was to identify philosophical schools of thought and theories used in research on promoting the practice of exclusive breastfeeding. Methods A scoping review using Arksey and O'Malley's framework explored the phenomenon of exclusive breastfeeding practice promotion. Searches were conducted using CINAHL Plus full-text, PubMed, APA PsycInfo, and Academic Search Premier. Search terms included theory, philosophy, framework, model, exclusive breastfeeding, promotion, support, English, and publication between 2001-2022. Results The online search yielded 1,682 articles, however, only 44 met the inclusion criteria for the scoping review. The articles promoting exclusive breastfeeding used pragmatism (n = 1) or phenomenology (n = 2) philosophies and theories of self-efficacy (n = 10), theory of planned behaviour (n = 13), social cognitive theories (n = 18) and represented 16 countries. Theories of self-efficacy and planned behaviour were the most used theories. Conclusions This review suggests that theories and models are increasingly being used to promote exclusive breastfeeding. Orienting exclusive breastfeeding programmes within theoretical frameworks is a step in the right direction because theories can sensitize researchers and practitioners to contextually relevant factors and processes appropriate for effective exclusive breastfeeding strategies. Future research should examine the efficacy and effectiveness of theory-informed exclusive breastfeeding programmes over time. Such information is important for designing cost-effective EBF programmes.